Risk Assessment of Pectenotoxins in New Zealand Bivalve Molluscan Shellfish, 2009–2019 - Michael J. Boundy; D Tim Harwood; Andreas Kiermeier; Cath McLeod; Jeane Nicolas; Sarah Finch (Toxins, 2020)
Pectenotoxins (PTXs) are produced by Dinophysis spp., along with okadaic acid, dinophysistoxin 1, and dinophysistoxin 2. The okadaic acid group toxins cause diarrhetic shellfish poisoning (DSP), so are therefore regulated. New Zealand currently includes pectenotoxins within the DSP regulations. To determine the impact of this decision, shellfish biotoxin data collected between 2009 and 2019 were examined. They showed that 85 samples exceeded the DSP regulatory limit (0.45%) and that excluding pectenotoxins would have reduced this by 10% to 76 samples. The incidence (1.3%) and maximum concentrations of pectenotoxins (0.079 mg/kg) were also found to be low, well below the current European Food Safety Authority (EFSA) safe limit of 0.12 mg/kg. Inclusion within the DSP regulations is scientifically flawed, as pectenotoxins and okadaic acid have a different mechanism of action, meaning that their toxicities are not additive, which is the fundamental principle of grouping toxins. Furthermore, evaluation of the available toxicity data suggests that pectenotoxins have very low oral toxicity, with recent studies showing no oral toxicity in mice dosed with the PTX analogue PTX2 at 5000 µg/kg. No known human illnesses have been reported due to exposure to pectenotoxins in shellfish, a fact which combined with the toxicity data indicates that they pose negligible risk to humans. Regulatory policies should be commensurate with the level of risk, thus deregulation of PTXs ought to be considered, a stance already adopted by some countries.